Gestão do desperdício têxtil e consumo sustentável: estratégias para mitigar os impactos da moda - Razante, Giovanna Medina (Universidade Federal de São Carlos, 2025)
The fashion industry, with its hegemonic fast fashion model, is configured as one of the sectors with the greatest global environmental impact, given the intense exploitation of natural resources, the massive generation of textile waste, and a significant carbon footprint. This study critically investigated textile waste management and sustainable consumption, analyzing the systemic failures of fast fashion and exploring strategies for the transition toward the Circular Economy (CE). The methodology adopted was a systematic literature review, which allowed for the identification of the intrinsic challenges of the linear model, the understanding of the evolution of the consumer's role, and the analysis of the opportunities and technological barriers for CE implementation, in addition to discussing the interdependence of integrated solutions. The research demonstrated that the logic of perceived obsolescence and the externalization of environmental costs drives a systemic crisis. However, the study also revealed growing consumer awareness and the transformative potential of the CE, enabled through innovations in design, new business models (such as rental and resale), and advanced technologies for fiber-to-fiber recycling, automated sorting, and digital traceability. In the Brazilian context, the implementation of these solutions faces striking challenges, including deficient recycling infrastructure, regulatory gaps in Extended Producer Responsibility (EPR), and socioeconomic barriers that limit access to sustainable fashion among lower-income classes. It is concluded that overcoming these obstacles and promoting more conscious and responsible consumption demand a multifaceted approach, which articulates structured public policies, investment in technological innovation, and continuous engagement of all stakeholders, aiming at the construction of a more equitable, resource-efficient, and environmentally regenerative future for the fashion sector.
Textile waste management and sustainable consumption: strategies to mitigate impacts of fashion
Keywords: Desperdício têxtil; Consumo sustentável; Economia circular; Impactos ambientais; Textile waste; Fast fashion; Circular economy; Environmental impacts; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; 11. Cidades e Comunidades Sustentáveis; 12. Consumo e Produção Responsáveis; 13. Ação contra a Mudança Global do Clima